Electronmicroscopic changes of the testes at the early stages after experimental thermal injury. - Mykha, S. Yu.; Volkov, K. S.; Nebesna, Z. M.; Kramar, S. B. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Severe thermal injuries accompanied by the development of endogenous intoxication, causing severe structural and metabolic disorders not only of the skin, but of all organs and body systems of burned organism. But lesser known submicroscopic changes of testis – the central organ of male reproductive system in dynamics after burn injury. Objective. The aim of this work was to established ultrastructural reorganization of the testes at early stages after experimental thermal injury. Methods. Experiment has been carried out on 20 mature white rats-males. Burn applied under ketamin anesthesia for 18-20% of hairless body surface of animals. Histological studies indicate the development of third-degree burn of skin. Experimental animals were decapitated on the 1st, 3th and 7th days of the experiment (early stage of shock and toxemia). Collecting the material for electronmicroscopic research conducted under the conventional method. Results. Electronmicroscopic research of the testes on the 1st day after thermal injury (stage of shock) detected adaptive-compensatory reorganization of the structural components of organ. Arterioles, venules and hemocapillaries have expanded lumens filled with blood cells, mainly erythrocytes. Vessel walls are irregularly thickened due to swelling of the endothelial cytoplasm and basement membrane. There are degranulation and mitochondrial hypertrophy in the cytoplasm of a part of Leydig cells that have perivascular location. There are also signs of reorganization of spermatogenic epithelium. Small amount of spermatogonia with signs of mitosis are available. Sertoli cells are moderately changed. Primary and secondary spermatocytes include round nucleus that have euchromatin and small clumps of heterochromatin in carioplasm, and small amount of organelles in the cytoplasm. Some spermatids and spermatozoa have damage structure of acrosome, observed high electron density of nucleus. At the early stage of toxemia (3th, 7th day of experiment) detected signs of destructive changes in the blood capillaries of the stroma and structural components of convoluted seminiferous tubules of the testes of experimental animals. Conclusion. Under burn shock ultrastructural reorganization of microcirculatory bed, walls of convoluted tubules and spermatogenic epithelium has adaptive-compensatory character. At the early stage of toxemia thermal lesions of animals skin lead to destructive changes in the blood capillaries, endocrinocytes, submicroscopic organization of structural components of the convoluted seminiferous tubules.